1972
DOI: 10.1111/j.1471-4159.1972.tb01346.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Thymidine Kinase in the Developing Rat Brain

Abstract: Abstract— Thymidine kinase (ATP: thymidine‐5′‐phosphotransferase EC 2.7.1.21) of the supernatant fraction from 6‐day‐old rat brain possessed a pH optimum of 8.0 and required the presence of 5mM‐ATP and 2.5 mM‐MgCl2 for maximum activity. The activity was completely inhibited by addition of 1.8 mM‐TTP. The enzyme activity was lost if the same supernatant fraction was refrozen and thawed. Km was 2.8 × 10−6 M for [6‐3H]thymidine. Following subcellular fractionation of rat brain, the greatest proportion and highest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

1974
1974
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(17 citation statements)
references
References 26 publications
(1 reference statement)
2
15
0
Order By: Relevance
“…Although control of DNA synthesis may involve many factors, our findings are consistent with the concept of Bollum and Potter (8) and Bianchi et al (6) that thymidine kinase may be considered as the essential regulatory control enzyme in the rate of DNA synthesis as demonstrated in regenerating rat liver, and that there may be a similar mechanism during brain development (26,32). Pratt and Aranow (23) observed that, in a study of cultured fibroblasts, inhibition of thymidine incorporation by cortisone may result from inhibition of DNA polymerase.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Although control of DNA synthesis may involve many factors, our findings are consistent with the concept of Bollum and Potter (8) and Bianchi et al (6) that thymidine kinase may be considered as the essential regulatory control enzyme in the rate of DNA synthesis as demonstrated in regenerating rat liver, and that there may be a similar mechanism during brain development (26,32). Pratt and Aranow (23) observed that, in a study of cultured fibroblasts, inhibition of thymidine incorporation by cortisone may result from inhibition of DNA polymerase.…”
Section: Discussionsupporting
confidence: 79%
“…(32) and Breitman (10) as modified for use in this laboratory in conjunction with other enzyme assays in rat brain tissue.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in vivo studies found that TK is required for viral replication in neural tissues (TG and brain), but not in peripheral tissues, of immunocompetent adult mice (4,(11)(12)(13)(14). Therefore, it is generally believed that adult neurons are postmitotic cells that do not express detectable levels of cellular TK, which presumably supports TK Ϫ HSV-1 to replicate in dividing cells (10,15). This notion is supported by our work showing that the replacement of viral tk with cellular tk enables HSV-1 to replicate in TG (16) and that providing TK activity in trans by coinfection with wild-type virus enables the TK Ϫ mutant to replicate in TG (17).…”
mentioning
confidence: 99%
“…Thymidine kinase was assayed by a procedure combining the method of Yamagami et al (22) and Breitman (2), as modified for use in our laboratory (19). Other activities were assayed as follows: ATC by a modification of the method described by Bethell et al (I), UK by the Herbst et al (7) modification of the method of Skold (15), and thymidylate synthetase as described by Kawai and Hillcoat (9).…”
Section: Methodsmentioning
confidence: 99%